Creative Industry Development Strategy for Home Culinary Businesses - Suryari Purnama; Hikmal Baedowi; Yansha Juliano Putrasetia (Pandawan Sejahtera Indonesia, 2023)
By relying on ideas and knowledge from human resources as the main key in driving economic activity, economic activity is required to intensify information and creativity to support the flow of creative industries. Because they control and oversee family finances, housewives are usually important members of society. Due to various constraints, such as family finances, caring for the family at home, etc., housewives cannot fully realize their ability to support the family's economy. However, there are problems, especially the dynamics of the world economy that are constantly changing, which also have an impact on Indonesia, which is also experiencing an economic crisis. In addition, this has an impact on uncertain and unpredictable market conditions. Even though people's purchasing power has fluctuated, this industry continues to thrive and even seems to be growing. The Industrial Revolution 4.0 which led to advances in science and technology and changed human perceptions of life, also had an impact on world economic development. The purpose of this research is to expand the business of housewives so they can build an independent society.